Loss of Occludin Expression and Impairment of Blood-Testis Barrier Permeability in Rats with Autoimmune Orchitis: Effect of Interleukin 6 on Sertoli Cell Tight Junctions - Pérez, Cecilia Valeria (2012)
Inflammation of the male reproductive tract is accepted as being an important etiological factor of infertility. Experimental autoimmune orchitis (EAO) is characterized by interstitial lymphomononuclear cell infiltration and severe damage of seminiferous tubules with germ cells that undergo apoptosis and sloughing. Because the blood-testis barrier (BTB) is relevant for the protection of haploid germ cells against immune attack, the aim of this study was to analyze BTB permeability and the expression of tight junction proteins (occludin, claudin 11, and tight junction protein 1 [TJP1]) in rats during development of autoimmune orchitis. The role of IL6 as modulator of tight junction dynamics was also evaluated because intratesticular content of this cytokine is increased in EAO rats. Orchitis was induced in Sprague-Dawley adult rats by active immunization with testicular homogenate and adjuvants. Control rats (C) were injected with saline solution and adjuvants. Untreated (N) rats were also studied. Concomitant with early signs of germ cell sloughing, a reduced expression of occludin and delocalization of claudin 11 and TJP1 were detected in the testes of rats with EAO compared to C and N groups. The use of tracers showed increased BTB permeability in EAO rats. Intratesticular injection of IL6 induced focal testicular inflammation, which is associated with damaged seminiferous tubules. Rat Sertoli cells cultured in the presence of IL6 exhibited a redistribution of tight junction proteins and reduced transepithelial electrical resistance. These data indicate the possibility that IL6 might be involved in the downregulation of occludin expression and in the modulation of BTB permeability that occur in rats undergoing autoimmune orchitis